Broad-scale wood degradation dynamics in the face of climate change : a meta-analysis - Chagnon, Catherine; Moreau, Guillaume; Bombardier-Cauffopé, Christine; Barrette, Julie; Havreljuk, Filip; Achim, Alexis (GCB Bioenergy, 2023)
In the context of global change, a better understanding of the dynamics of wood degradation, and how they relate to tree attributes and climatic conditions, is necessary to improve broad-scale assessments of the contributions of deadwood to various ecological processes, and ultimately, for the development of adaptive post-disturbance management strategies. The objective of this meta-analysis was to review the effects of tree attributes and local climatic conditions on the time since death of coarse woody debris ranging in decomposition states. Results from our meta-analysis showed that projected warming will likely accelerate wood decomposition and significantly decrease the residence time in decay stages. By promoting such a decrease in residence time, further climate warming is very likely to alter the dynamics of deadwood, which in turn may affect saproxylic biodiversity by decreasing the temporal availability of specific habitats. Moreover, while coarse woody debris has been recognized as a key resource for bioenergy at the global scale, the acceleration of decay-stages transition dynamics indicates that the temporal window during which dead trees are available as feedstock for value-added products will shrink. Consequently, future planning and implementation of salvage harvesting will need to occur within a short period following disturbance, especially in warmer regions dominated by hardwood species. Another important contribution of this work was the development of a harmonized classification system that relies on the correspondence between the visual criteria used to characterize deadwood decomposition stages in locally developed systems the literature. This system could be used in future investigations to facilitate direct comparisons between studies. Our literature survey also highlights that most of the information on wood decay dynamics comes from temperate and boreal forests, whereas data from subtropical, equatorial and subarctic forests are scarce. Such data are urgently needed to allow ...